Analisis Kinerja Keuangan Berdasarkan Rasio Keuangan Pada Perusahaan Umum Daerah Tirta Mayang Kota Jambi Tahun 2021-2023 - Mahardika, Raditya; Friyani, Rita; Wendry, Widya Sari (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to analyze the financial performance of PERUMDA Tirta Mayang Kota Jambi during the 2021–2023 period using financial ratio analysis, including profitability, liquidity, activity, and solvency ratios. The research method applied is descriptive quantitative with a case study approach focusing on a single subject. The results indicate that profitability ratios such as Gross Profit Margin (GPM), Net Profit Margin (NPM), and Return on Assets (ROA) have improved, reflecting enhanced efficiency and effectiveness in resource management. However, Operating Profit Margin (OPM) declined in 2022 before recovering in the following year. In terms of liquidity, the Current and Quick Ratios declined but remained within acceptable levels, while the Cash Ratio remained below ideal standards. Activity ratios such as Total Asset Turnover (TATO) were stable, Fixed Asset Turnover (FATO) decreased, and Working Capital Turnover (WCTO) showed significant improvement. For solvency, rising Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR) indicate increased reliance on debt financing. Overall, the company’s financial performance shows a positive trend, although certain aspects still require further attention.